Human dimensions of wildfires in NW Spain: causes, value of the burned vegetation and administrative measures - Calviño-Cancela, María; Cañizo-Novelle, Nuria (PeerJ, 2018)
Exploring the human dimensions of forest fires is a crucial, although often overlooked, aspect of wildfire research, since wildfires often have important socio-economic impacts and humans are nowadays the main cause of wildfires in many areas of the world. We carried out a telephone survey (N = 345 interviews) in one of the most fire-prone areas in Europe (NW Spain) in order to assess citizens’ awareness about wildfire causes and risks, their perception of the value of the vegetation and of administrative measures to fight against fires. Perceptions of respondents about fire causes were in general realistic although fires caused by pyromaniacs and for profit were overestimated, while vegetation management was comparatively underestimated. Citizens were broadly aware of the fire risk associated with different vegetation types, rightly considering native oak forests and agricultural fields as less risky than shrublands and pine and eucalypt plantations. Tree-dominated vegetation was more valued than treeless formations, and native forests more than tree plantations, which seems related to a preference for ecological value over utilitarian considerations. In addition, the value of eucalypt plantations was clearly affected by the education level of respondents, being less valued as the education level increased. Most citizens considered that the administration was not doing enough to fight against fires. The law that compels landowners to reduce fuels in wildland-urban interfaces was considered effective by most respondents (72%), but 50% considered it difficult to implement by landowners. This may explain the poor degree of compliance of this law.
Keywords: Forest fires; Survey; Public attitudes; Public opinion; Wildland-urban interfaces; Spain